Indonesian EFL Lecturers’ Performance and Attitude, and Their Pedagogical Implications in Teaching English in the Classroom Practices - Rahman, Ninik Wahyuni; Atmowardoyo, Haryanto; Salija, Kisman (Celebes Journal of Language Studies, 2023)
This research aimed at finding out the Indonesian EFL lecturers’ performance based on the students’ perceptions, exploring the EFL lecturers’ attitudes, and investigating their pedagogical implications in teaching English in classroom practices. This research applied mixed-method design; Concurrent Mixed Methods Strategy, with type Triangulation Concurrent Strategy. The population was the students of the English education department in the academic year 2021/2022 and the EFL lecturers in the same major at Institut Parahikma Indonesia, Gowa. The researcher used total sampling from students and lecturers. The instruments used were 2 kinds of questionnaires, an observation checklist, and documentation by video recording. The quantitative data were analyzed by using SPSS through descriptive statistics (percentages, mean scores, and standard deviations), and the quantitative-qualitative data were analyzed by using SPSS then through four stages; data collection, data condensation, data display, and drawing conclusions. Based on the results, the Indonesian EFL lecturers’ performance based on the students’ perceptions was categorized as effective and had good performance in teaching English. It showed in terms of planning, implementing, and evaluating the learning. Next, the EFL lecturers’ attitudes were proper and positive towards their teaching of English. It is supported by the performance and ability of the lecturers to increase the students’ motivation to learn through good collaboration with their students. Furthermore, the pedagogical implications of Indonesian EFL lecturers were appropriate to the principle of pedagogical competence in teaching English. It was cultivated through their performance, ability, as well as attitudes that affected and improved their students’ learning English outcomes in terms of grammar and pronunciation.